Does the Manufacturing Industry Reduce Poverty on Sumatra Island? - Mukhlis, Dr.; Suhel, Dr; Aulia, Yunita; Indah Lestari, Putri; Hamira (Jurnal Ekonomi Pembangunan, 2024)
Poverty alleviation is an important priority for governments. Encouraging manufacturing growth is often seen as an effective strategy to alleviate poverty. However, the impact of such growth on poverty rates in Sumatra Island remains unclear. This study analyze the impact of manufacturing growth on poverty rates in 10 provinces in Sumatra Island, using secondary data from 2008 to 2022. Using the quantitative approach and panel data regression analysis, the results show that industrial growth in Sumatra Island, although not significant, has an impact on poverty reduction. However, industrial growth can indirectly absorb labor. Labor and education variables have a negative and significant effect on poverty.  These findings highlight the need for policy interventions focusing on vocational education and training, infrastructure improvement, economic diversification, labor policies, and local community empowerment to effectively reduce poverty.